2011
DOI: 10.1099/ijs.0.020156-0
|View full text |Cite
|
Sign up to set email alerts
|

Rhizobium tubonense sp. nov., isolated from root nodules of Oxytropis glabra

Abstract: Four rhizobial strains, designated CCBAU 85046 T , CCBAU 85051, CCBAU 85048 and CCBAU 85049, isolated from root nodules of Oxytropis glabra grown in Tibet, China, were previously defined, using amplified 16S rRNA gene restriction analysis, as a novel group within the genus Rhizobium. To clarify their taxonomic position, these strains were further analysed and compared with reference strains of related bacteria using a polyphasic approach. The 16S rRNA gene analysis showed that the four isolates formed a distin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 36 publications
(42 reference statements)
0
4
1
Order By: Relevance
“…Similarly, the phylogenetic relationship between the type strain of Rhizobium tubonense and other recognized species of the genus Rhizobium based on the 16S rRNA gene was not in accordance with those obtained from analyses of the recA, atpD and glnII genes (Zhang et al, 2011a).…”
Section: Strain L6-16contrasting
confidence: 61%
See 1 more Smart Citation
“…Similarly, the phylogenetic relationship between the type strain of Rhizobium tubonense and other recognized species of the genus Rhizobium based on the 16S rRNA gene was not in accordance with those obtained from analyses of the recA, atpD and glnII genes (Zhang et al, 2011a).…”
Section: Strain L6-16contrasting
confidence: 61%
“…For example, phylogenetic analysis of the 16S rRNA gene indicated that Rhizobium subbaraonis JC85 T was closely related to Rhizobium borbori DN316 T , whereas phylogenetic analyses of the glnA and recA genes showed that R. subbaraonis JC85 T formed a cluster with Rhizobium huautlense LMG 18254 T and Rhizobium halophytocola YC6881 T (Ramana et al , 2013). Similarly, the phylogenetic relationship between the type strain of Rhizobium tubonense and other recognized species of the genus Rhizobium based on the 16S rRNA gene was not in accordance with those obtained from analyses of the recA , atpD and glnII genes (Zhang et al , 2011a).…”
mentioning
confidence: 84%
“…The genus Rhizobium (Frank, 1889) was the first and only rhizobial genus described for a century, before the genus Bradyrhizobium was reported (Jordan, 1982). Since then, a series of taxonomic changes have been made in the genus Rhizobium and at the time of writing it contains 47 species, including the recently described species Rhizobium soli (Yoon et al , 2010), Rhizobium borbori (Zhang et al , 2011b), Rhizobium vignae (Ren et al , 2011) and Rhizobium tubonense (Zhang et al , 2011a).…”
mentioning
confidence: 99%
“…These microbes have been isolated from various sources, with the majority being associated with fabaceous plants (Ló pez-Ló pez et al, 2012;Mnasri et al, 2014;Ren et al, 2011a, b;Rincó n-Rosales et al, 2013;Yao et al, 2012;Zhang et al, 2011b), although some are from non-fabaceous plants (Berge et al, 2009;Kittiwongwattana & Thawai, 2013Peng et al, 2008;Puławska et al, 2012;Zhang et al, 2014) and non-plant sources (Parag et al, 2013;Quan et al, 2005;Zhang et al, 2011a). At the time of writing, the genus Rhizobium comprises 70 recognized species.…”
mentioning
confidence: 99%